2018
DOI: 10.18632/oncotarget.25717
|View full text |Cite|
|
Sign up to set email alerts
|

Prosopis juliflora (Sw.), DC induces apoptosis and cell cycle arrest in triple negative breast cancer cells: in vitro and in vivo investigations

Abstract: Plant originated drugs/formulations are extensively prescribed by the physicians as a complementary therapy for treating various human ailments including cancer. In this study Prosopis juliflora leaves methanol extract was prepared and exposed to human breast cancer cell lines i.e. MDA-MB-231 and MCF-7 and human keratinocytes HaCaT as a representative of normal cells. Initially, a series of in vitro experiments like cell proliferation, migration, colony formation, cell cycle arrest and inhibition of angiogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…This extract was found to be rich in bioactive compounds such as terpenes and phytol, similar to the major compound detected in AELE. They revealed the efficient and selective anti-breast cancer activity against triple negative breast cancer cells (MDA-MB-231) [63], explaining the selective effect observed in our study.…”
Section: Discussionsupporting
confidence: 76%
“…This extract was found to be rich in bioactive compounds such as terpenes and phytol, similar to the major compound detected in AELE. They revealed the efficient and selective anti-breast cancer activity against triple negative breast cancer cells (MDA-MB-231) [63], explaining the selective effect observed in our study.…”
Section: Discussionsupporting
confidence: 76%
“…e leaves contain an amount of protein, carbohydrates, and mineral matter and have high nutritive value [17]. e methanol leaf extract of Prosopis not only can reduce tumor growth, but also present in vitro and in vivo anticancer ability [19]. e smoke of the Prosopis leaves can be applied for treating eye sickness [20].…”
Section: Prosopis Cultivation and Applicationsmentioning
confidence: 99%
“…Also, in the recent study by Ramazani et al [106], the outcomes displayed that the Pju has significant in vivo and in vitro anti-plasmodial activity. Gurushidhappa and coworkers [107] also investigated the anti-cancer activity of Pju under in vitro and in vivo conditions and reported that the methanolic extract of Pju leaves could suppress breast cancer cells by inducing apoptosis and cell cycle arrest [107]. However, these results provided a new window to carefully consider the secondary metabolites isolated from Pju for clinical therapies to develop a new class of safe and effective anti-cancer drugs.…”
Section: Pre-clinical Effectiveness: Paving the Way For Clinical Studiesmentioning
confidence: 99%